DECODING FEAR: SEMIOTIC INTERPRETATION OF CHILD IMAGERY IN INDONESIAN HORROR FILM POSTERS - Dini Anggraheni; Sahid Teguh Widodo; Mahendra Wijaya; Deny Tri Ardianto (Universitas Duta Bangsa Surakarta, 2026)
This study examines the representation of anxiety through child imagery in Indonesian horror film posters, employing Roland Barthes’ semiotic framework. The depiction of children as protagonists in horror movie posters creates a complex interaction between innocence and terror, utilizing visual clues to elicit emotions and capture viewers' attention. The objective of this study is to analyze how children's visual representations evoke sensations of fear and anxiety by interpreting their denotative and connotative meanings. A qualitative content study was conducted on ten meticulously selected Indonesian horror movie posters, spanning from Danur (2017) to Taghut (2024). The study concentrates on visual elements, including lighting, color palettes, body posture, face expressions, and symbolic objects, to uncover the fundamental cultural and psychological significances. The results indicate that child imagery serves as a powerful semiotic tool that embodies socio-cultural anxieties around family, morality, and social norms, while simultaneously amplifying terror through the contrast of vulnerability with supernatural or perilous elements. This research demonstrates the use of Barthes' semiotic theory in interpreting complex visual texts and enhances our comprehension of horror aesthetics within Indonesian cinema. The study offers significant insights for scholars examining media semiotics, visual culture, and film studies, particularly those interested in the dynamics of terror representation in cinematic marketing.